Education Probelematiaka and Driving Lecturer - Kirtawadi Kirtawadi; Abdul Fattah; Mustain Mustain (Universitas Muhammadiyah Enrekang, 2024)
Training is very likely the most important thing in human existence. Every individual has the choice to get sufficient and impartial training. However, what happens in Indonesia is an educational gap for every Indonesian citizen. In addition, so far what has been observed is that the school system in force in Indonesia is considered inflexible and incapable. We can see this from the lagging quality of education in Indonesia compared to other countries. The education system used in Indonesia is not much different from the education system in other countries. The main difference is the mistakes during field training. Many fundamental mistakes create a gap between the objectives of the school system and its implementation in the field. Which ultimately makes a large number of these goals unable to be achieved and completed properly. This test aims to find out the problems of the school system in Indonesia as well as the fundamental mistakes and answers to each current problem. framework problems.